2017
DOI: 10.1007/s40290-017-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Additional Risk Minimisation Measures for Medicinal Products in the European Union: A Review of the Implementation and Effectiveness of Measures in the United Kingdom by One Marketing Authorisation Holder

Abstract: IntroductionAdditional risk minimisation measures (aRMMs) for medicinal products are necessary to address specific important safety issues which may not be practically achieved through routine risk management measures alone. The implementation and determination of effectiveness for aRMMs can be a challenge as it involves multiple stakeholders. It is therefore important to have concise objectives to avoid undue burden on patients, healthcare professionals and the healthcare system.AimThe aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…However, despite many strengths, surveys also have limitations [24]. The low response rates from surveys suggest that providing feedback on a voluntary basis does not always achieve the desired level of response [33]. Many limitations are illustrated by this survey.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, despite many strengths, surveys also have limitations [24]. The low response rates from surveys suggest that providing feedback on a voluntary basis does not always achieve the desired level of response [33]. Many limitations are illustrated by this survey.…”
Section: Discussionmentioning
confidence: 95%
“…A review of all completed aRMM evaluation surveys (classified as PASS) from the EU PAS Register found that only 2 of 11 cross-sectional surveys selected 80% as a predefined threshold of success [23]. Better understanding of the suitable thresholds for aRMM success [33] and whether these thresholds differ by stakeholder, specialty, risk, or other factors, would be valuable when making conclusions about the program's effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…administration errors) can be difficult to identify in such data. Surveys to investigate whether HCPs understand the material may be biased, as HCPs who are more aware of the educational material may be more inclined to participate in such a survey [28]. In addition, it is possible that those who read the material, but also experienced the ME, are less likely to participate because of social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that for most CAPs in our dataset, studies to assess the effectiveness of aRMMs for MEs were agreed upon. However, only a few effectiveness studies concerning MEs have been published in publicly available domains [28,29]. Public availability of these studies could help develop new techniques to measure the effectiveness of aRMMs and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the safety concerns related to medicinal products may be assuaged with routine RMMs, including pack size restrictions, adequate wording in patient information leaflets (PILs) which are included in the pack with medicine, and a summary of product characteristics (SmPC)-a legal document approved as part of the marketing authorization of a medicinal product, which includes information for healthcare professionals on how to use the medicine 9 .…”
Section: Commentarymentioning
confidence: 99%